Carbon meta-nanotubes synthesis, properties and applications - Monthioux, Marc (John Wiley & Sons, 2012)
"The book will present different chapters corresponding to each of the meta-nanotube categories. There will be an introductory chapter that will provide the basics of what is needed to be known about pristine nanotubes to understand what is in the subsequent chapters. Each of the chapters that follow the introductory chapter will cover aspects from synthesis to applications, characterization, behavior, properties, and mechanisms. These chapters will focus on heterogeneous nanotubes, doped nanotubes, functionalized nanotubes, coated nanotubes and hybrid nanotubes, respectively, and will be followed by a final concluding chapter"--